Umowa powierzenia parafii instytutowi zakonnemu: uwagi ogólne - Skonieczny, Piotr (Poznańskie Studia Teologiczne, 2014)
This article presents the general and theoretical problem concerning the agreement (conventio) entrusting a parish to a clerical religious institute or to a clerical society of apostolic life (canon 520 of the 1983 Code of Canon Law). The author distinguishes contractus from conventio in the Latin Code now in force, considering the agreement specified in canon 520 of the 1983 Code as a public law contract. He then analyzes the parties to this agreement and rejects the opinion that canon 520 of the 1983 Code could be applied directly to religious entities other than those specified in the above canon. Finally, the author analyzes the essentialia conventionis, i.e. the essential and sufficient elements of the commented agreement: quae actum ipsum essentialiter constituunt (canons 124 § 1 and 520 § 1 of the 1983 Code). According to the author three elements are necessary to reach the consensus between parties to the agreement: (1) the designation of the parties in accordance with canon 520 of the 1983 Code; (2) the essence of the agreement: the commitment of a parish, consisting in the pastoral care of the Christian faithful who form the community; (3) the specification of the entrusted parish as an object of the commitment. Lastly, the author criticizes the legal technicalities adopted in the commented canon.